GOOD FAITH PRINCIPLE UNDER ARTICLE 7 OF CONVENTION ON CONTRACTS FOR INTERNATIONAL SALE OF GOODS (CISG) IN BONAVENTURE V. PAN AFRICAN EXPORT CASE - Lucya Agustine Nindhy Utami; Lena Farsia (Universitas Syiah Kuala, 2022)
This paper aims to discover the effectiveness of the good faith principle when it is related to cases, in particular Bonaventure V. Pan African Export Case. Additionally this paper assess to whether each country have a similar comprehension of the importance and execution of the good faith principle in article 7 of CISG as a source in contract or agreement between parties. This paper utilised normative legal research which focusing to explore legal norm of the issue. The outcomes showed that good faith principle has been understood differently in different country. The implementation of the agreement that has been agreed upon by both parties can also change due to factors within the country that cannot be equated even though they have followed the good faith principle.